Cyberbullying em jogos online – categorização dos conteúdos, levantamento nacional dos jogadores e perfil das vítimas - Carvalho, Evelise Galvão de (2014)
This research was split into three studies which had as the main objective to analyze and understand cyberbullying within the game, League of Legends. The first study investigated 250 games, by tribunal, of League of Legends; the content, and insults used for the practice of cyberbullying in League of Legends. Cyberbullying showed up in the form of direct insults, racism, prejudice, indirect insults, and profanity. The word "Trash", and its variations, were the insults more often used (fi = 1.79) per game followed by Noob (fi = 1.15). All these terms were been categorized and classified in the current legislation in Brazil, to analyze the feasibility of possible punishment of offenders. The second study focused on the national survey (n = 1348) of the League of Legends’ players using an online questionnaire regarding their demographics, victimization and consequences of these abuses. A large portion of the players are from Southeast (52 %) of Brazil; 90 % said they had been victims of violence in the last week, and 23% had their daily activities affected by aggressions within the game. The third study (n=3) profiled the victims of cyberbullying by interview and psychological inventories, results showed that participants underwent at risk parenting styles and had a history of being victims of bullying during childhood and adolescence.